Harnessing essential oils through nanotechnology-based drug delivery systems for biomedical applications: current trends and future prospects - Laxmi Gharti; Neelam Kumari; Vishal Sharma; Navneet Kumar Upadhyay; Hemlata Kaurav (Creative Pharma Assent, 2026)
Background: Essential oils (EOs) have been used in therapeutic applications for centuries and continue to be popular in modern complementary and alternative medicine. EOs are highly concentrated, plant-derived volatile components with a wide range of biological activities, including analgesic, antibacterial, antifungal, antiviral, anti-inflammatory, and antioxidant activities. This study aims to review novel drug delivery systems enriched with essential oils to improve therapeutic outcomes, overcoming the limitations of the phytoconstituents, including high volatility, hydrophobicity, instability, and toxicity. Methodology: A literature review was conducted using globally recognized scientific research databases, including Google Scholar, PubMed, and Scopus. Studies were selected for their enhanced therapeutic applications of essential oils through novel drug delivery systems. The search strategy included keywords such as “essential oils”, “nanoformulations”, “nanoemulsions”, “liposomes”, and “solid lipid nanoparticles”, combined using Boolean operators (AND/OR). Articles published in English between 2021 and 2026 were considered. Result and Discussion: Encapsulation of EOs in nanocarriers and lipid-based vesicle systems enhances their bioavailability, improves their stability, and controls their release profile. The progressive nanotechnologies in the drug delivery system have advanced EO’s potential therapeutic approach for treating various disorders such as microbial diseases, pain, stomach disorders, depression, cancer, and many more. This review describes the potential of novel drug delivery systems to overcome the existing challenges associated with phytoconstituents. Conclusion: Novel drug delivery systems for EOs have the potential to improve the efficacy and safety of EO-based therapeutics. In this review, various novel drug delivery systems that have been reported to enhance the therapeutic potential of EOs by overcoming their limitations are highlighted.